"Homeliness, hope and humour" (H3) – ingredients for creating a therapeutic milieu in prisons. Issue 1 (9th April 2018) - Williams, Ian; Winship, Gary
Abstract : Purpose: The purpose of this paper is to build a new theoretical framework for inscribing the constituents of therapeutic community (TC) practice in prisons and other secure psychiatric settings looking at three core element: homeliness, hope and humour. Design/methodology/approach: The study is based on theory building, review of related literature, including research and policy, and synthesis from related funded research projects (Sociology of Health and Illness, Arts Humanities Research Council). Findings: Home-as-method, and the concept of transitional home, highlights how a well-designed therapeutic environment looks and feels and can act as a base for effective rehabilitation. The TC aspires to offer a corrective new synthesis of home superseding the resident's prior experience. A through-going definition of hope-as-method is outlined. It is argued that hope is co-constructed on the TC, and that there is a necessary challenge in gauging fluctuations in hope across time. Humour is a much overlooked idea but arguably an integral ingredient of healthy transactions between prisoners and staff. The particularities of humour present a challenge and an opportunity for harnessing the conditions when humour can flourish and conversely, the chain of events when mal humour damages community atmosphere. Practical implications: H 3 provides a new framework for reflecting on current TC practice, and also a model for developing novel ways of seeing, including the development of research and policy guidance. H 3 also provides a philosophical base for developing a curriculum for education and training. Originality/value: The 3Hs offers a rubric for positively narrating the aspirations of a prison milieu. The idea is purposively simple, and so far the authors have found that staff, prisoners and service directors are receptive to the concept, and there are plans for the 3Hs are set to be a narrative descriptor for developing practice in prisons.